2009 IEEE 12th International Conference on Computer Vision 2009
DOI: 10.1109/iccv.2009.5459412
|View full text |Cite
|
Sign up to set email alerts
|

3D open-surface shape correspondence for statistical shape modeling: Identifying topologically consistent landmarks

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The landmarks were selected automatically in order to cover the entire surfaces uniformly. The correspondences were initially obtained using constrained k‐mean clustering and refined by minimizing the matching cost using shape contexts …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The landmarks were selected automatically in order to cover the entire surfaces uniformly. The correspondences were initially obtained using constrained k‐mean clustering and refined by minimizing the matching cost using shape contexts …”
Section: Methodsmentioning
confidence: 99%
“…d). The matching transformations were determined similarly to Step 1, by preregistering the template and individual surfaces using cylinder or plane fits and by determining correspondences between landmarks in the template and individual surfaces using constrained k‐mean clustering and shape contexts …”
Section: Methodsmentioning
confidence: 99%
“…An optimization technique for improving the correspondence, called "iterative landmark sliding" (SLIDE), has shown to be better than other approaches such as minimum description length (MDL) and spherical harmonics (SPHARM), in terms of the three shape model evaluation measures (compactness, generalization, and specificity) (Dalal et al, 2009(Dalal et al, , 2007. While the SLIDE optimization was not considered in the current study, it has been shown that the correspondence map established using coordinates and surface normals along with iterative TPS to refine landmarks is sufficient Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In [43,4951], they use Dijkstra's algorithm to define patches. It will lead to zigzag boundaries along the patches.…”
Section: Discussionmentioning
confidence: 99%